2018
DOI: 10.1080/00016357.2018.1460490
|View full text |Cite
|
Sign up to set email alerts
|

Low reproducibility between oral radiologists and general dentists with regards to radiographic diagnosis of caries

Abstract: The reproducibility between specialists in oral radiology and general dentists for detecting caries in DPTs was low.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…As a retrospective study, it was not possible to obtain a gold-standard for the conditions assessed. However, previous studies comparing observers' experience showed good reproducibility for specialists (1) or professionals with more than five years dealing with imaging diagnosis (2). An important point to emphasize is that the image alone is not responsible for the correct diagnosis.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…As a retrospective study, it was not possible to obtain a gold-standard for the conditions assessed. However, previous studies comparing observers' experience showed good reproducibility for specialists (1) or professionals with more than five years dealing with imaging diagnosis (2). An important point to emphasize is that the image alone is not responsible for the correct diagnosis.…”
Section: Discussionmentioning
confidence: 95%
“…An important point to emphasize is that the image alone is not responsible for the correct diagnosis. It is dependent on the observer's experience (1,2) and the evaluation method used (5), among other factors that might have influence, such as the subjectivity of this task. It is noticeable the change in diagnostic thinking according to the evaluation method used in the present study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Clinical examination is the main method for caries detection, with radiographic examination being a complementary diagnostic tool [40]. According to experience and scientific literature, intraoral bitewing images are the most effective in detecting caries lesions [41]. However, only one study included in this review employed bitewings to detect caries.…”
Section: Discussionmentioning
confidence: 99%
“…The neural network achieved an accuracy rate of 85%. Neural networks may be valuable for evaluating radiographic bone loss and generating image-based periodontal diagnostics [ 24 ].…”
Section: Related Workmentioning
confidence: 99%